Icelandic companies doing business in China : cultural differences and intercultural communication - Inga Dís Júlíusdóttir 1989- (2015)
It has been recognized that doing business is China is particularly difficult. Business practices can be problematic because of cultural differences and communication barriers. Over the years, the relationship between Iceland and China has been on good terms and recently, in 2013, these two countries signed a Free Trade Agreement (FTA). It is expected that business between Iceland and China is going to increase because more companies are searching for various opportunities and looking towards China to tap into various benefits of the FTA. In this research cultural differences and intercultural communication are analyzed though previous research, survey questionnaire, and interviews to find out how they are affecting Icelandic businesses doing business in China. This research reveals that cultural and communication barriers are always present and need to be constantly managed. One of the key findings is that Icelandic companies seems to recognize the advantage from overcoming cultural differences and communication barriers, but are however not doing enough to address the challenge, resulting in financial loss.